High Resolution Remote Sensing Data Application to Assess Parking Space in Urban Area - Suharyadi Suharyadi; Iswari Nur Hidayati (Indonesian Journal of Geography, 2020)
The increase population in a large city such as Yogyakarta has caused an increase in the number of cars. The large number of cars created another problem of limited parking space in the city. Currently, there is a lack of a spatial approach to solve the problem of parking space. With the availability of high-resolution remote sensing data, the business area in the city can be mapped accurately. This study aims to map the business zone in Yogyakarta City and to estimate the needs of parking space for trade, service, and education centers in Yogyakarta City using remote sensing imagery. The business zone really needs a parking area because many people as producers for loading goods and consumers buy at these stores. The method used to estimate the vehicle parking space requirement is a combination of field surveys and the interpretation of remote sensing images. The field survey was used to obtain the characteristics of the visitors, and the volume of filled parking space. Meanwhile, remote sensing imagery was used to obtain spatial data of land use. The parking requirements of commercial buildings are 2.25-3.15 spaces per 100 m2, offices are 1.0-1.60 spaces per 100 m2, hotels are 0.25-0.35 spaces for each sleeping room, theaters are 0.06 spaces for every seat, hospitals are 0.60 spaces for each bed, and schools are 0.10 space for every student. This paper demonstrated the use of remote sensing to solve urban vehicle problems, and such information can be used for city planning.